2009
DOI: 10.4076/1757-1626-2-6809
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis mimicking acute coronary syndrome following influenza B virus infection: a case report

Abstract: We present a notable case of a 15-year-old male infected with influenza B virus who showed the clinical manifestations of myocardial ischemia. He was admitted to our hospital with sudden chest pain. He had febrile illness for the past 2 days. Rapid antigen test for influenza revealed positive influenza B virus antigen. The initial electrocardiogram showed elevation of the ST-segments in leads II, II, aVF and reciprocal depression in leads V1 and V2. Serum test showed elevation of creatine kinase and troponin T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Other extrapulmonary complications include central nervous system involvement, such as viral encephalitis and encephalopathy, gastrointestinal symptoms, or myositis (Craver et al, 1997; Frank et al, 2010; Muneuchi et al, 2009; Newland et al, 2003; Tabbutt et al, 2004; Wright, 2006). Additional studies designed specifically for populations with influenza B virus infections are needed to properly estimate the burden of complications.…”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%
“…Other extrapulmonary complications include central nervous system involvement, such as viral encephalitis and encephalopathy, gastrointestinal symptoms, or myositis (Craver et al, 1997; Frank et al, 2010; Muneuchi et al, 2009; Newland et al, 2003; Tabbutt et al, 2004; Wright, 2006). Additional studies designed specifically for populations with influenza B virus infections are needed to properly estimate the burden of complications.…”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%
“…A combination of direct cytolytic effects of the influenza virus/host immune response is thought to be responsible for the overall pathologic changes in acute influenzal myocarditis. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Of the many causes of viral myocarditis, influenza A and B are not the most common causes but are important. The clinical presentation of myocarditis is often subtle, and the only sign is often unexplained tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial biopsies reveal inflammatory infiltrates with or without necrosis. [10][11][12][13][14][15][16][17][18][19][20] Myocarditis is a recognized complication of viral influenza. 7,[10][11][12][13][14][15]18 Viral myocarditis due to influenza runs the clinical spectrum from asymptomatic disease with only electrocardiographic or echocardiographic abnormalities to fulminant/fatal myocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Muneuchi et al reported that myocarditis associated with influenza B virus appeared to be caused by endothelial impairment and disturbance of microcirculation rather than direct injury to cardiac myocytes. 22 These findings suggest that a negative quick diagnostic test of patients with systemic symptoms might lead to hospitalization due to symptomatic viral pneumonia, or myocarditis, and the pathogenesis of systemic complications of influenza might be related to the induction of inflammatory cytokines produced by infected alveolar cells.…”
Section: Influenza a (H1n1) 2009 Myocarditis In Japanmentioning
confidence: 99%